Green Fuel as Alternative Fuel for Diesel Engine: A Review - Mohd Fahmi, Othman; Abdul Adam, Abdullah; G., Najafi; R., Mamat (Elsevier, 2017)
Green fuels also called green hydrocarbons, biofuels, are fuel produced from biomass sources through a variety of biological and thermochemical processes. These products are similar to petroleum gasoline and diesel fuels and are therefore considered fully infrastructure compatible fuels. They can be utilized in engines without engine modiﬁcation. This paper presents a comprehensive review on the potential of biodiesel from diﬀerent waste feedstock biodiesel such as waste cooking oil and waste plastic oil. Furthermore, the eﬀect on the engine performance, combustion and exhaust emissions including details of engine and operating condition also review in this paper. The main goal of this paper is to provide information to the engineers, industrialists and researchers who are interested on waste biodiesel and to prominence waste biodiesel as a promising alternative replacement for fossil fuels. A large number of literatures from highly rated journals in scientiﬁc indexes are reviewed including the most recent publications.